Arabic Translation, Stylistic And Rhetorical: Manhood In The Hadith - Sobhy Ebrahim Elmelegy (Ijaz Arabi Journal of Arabic Learning, 2023)
The main objective of this paper is to define “al-rujoolah” (manhood) and its contexts in the primary Arabic literature that it Prophet Muhammad's (peace be upon him) Hadith. The project's goal is to comprehend the significance of this subject in the Prophet's statement and to contribute to the library of Arabic rhetorical and scientific work related to this Hadith, which includes a rhetorical lesson, stylistic analysis, and reveals the ornamental characteristics and stylistic features. The study used an analytical method based on analyzing, interpreting, and comparing how the Quran and prophets talked about this trait and its signs. Also, talk about the different stories in the Hadith to figure out what they mean. The word “al-rujoolah” in "seven people to whom Allah will give His shade on the day when there will be no shade but the shade of His throne (on the day of resurrection)."  provides the meaning of “perfection of personality and its idealism," which appears in particular situations. This study showed the were and what other qualities the Prophet wanted Muslims to have in their everyday lives. The rhetorical lesson gives a style analysis and shows how the Prophet's statement about the uses of this word shows off his style and rhetorical skills. "Al-Rujolah" means "perfection of personality and its idealism," which appears in particular situations.